Issue Management in Maintaining Digital Campus Reputation (Insan Cita Indonesia University Case Study in Facing Cyber Attacks in 2022) - Ardina, Nike (Program Studi Ilmu Komunikasi FBIK Unissula, 2024)
AbstractAs the first digital campus in Indonesia and carrying a brand image as a university at the forefront of digital technology, UICI faced challenges with cyber attacks in the form of hacking of UICI's social media accounts. This attack not only has the potential to lose UICI's digital assets in the form of Instagram, but also has the potential to damage its reputation. So in handling and dealing with this potential crisis, UICI must manage the circulating issues so that they do not become a crisis. This research uses a qualitative approach and case study method with data collection techniques in the form of observation and documentation studies. The research results found that in managing issues, UICI formed a crisis team and appointed one person as a spokesperson who then succeeded in turning the situation around with proper issue management. This cyber attack provides an opportunity for UICI to prove the campus' brand image with technology. From this research, it is recommended for both UICI and other institutions to implement multi-layered security for digital asset managers. As well as forming guidelines in the form of strategies and management plans for the digital assets owned. Keywords: Digital Campus, Brand Image, Reputation, CyberAttacks, Issue Management AbstrakSebagai kampus digital pertama di Indonesia dan mengusung brand image sebagai perguruan tinggi terdepan dalam teknologi digital, UICI menghadapi tantangan berupa serangan siber berupa peretasan akun media sosial UICI. Serangan ini tidak hanya berpotensi meruginya aset digital UICI berupa Instagram, tetapi juga berpotensi merusak reputasinya. Maka dalam menangani dan menghadapi potensi krisis ini, UICI harus mengelola isu-isu yang beredar agar tidak menjadi krisis. Penelitian ini menggunakan pendekatan kualitatif dan metode studi kasus dengan teknik pengumpulan data berupa observasi dan studi dokumentasi. Hasil penelitian menemukan bahwa dalam mengelola isu, UICI membentuk tim krisis dan menunjuk satu orang sebagai juru bicara yang kemudian berhasil membalikkan keadaan dengan manajemen isu yang tepat. Serangan siber ini memberikan kesempatan bagi UICI untuk membuktikan brand image kampus dengan teknologi. Dari penelitian ini, direkomendasikan bagi UICI dan institusi lain untuk menerapkan keamanan berlapis bagi pengelola aset digital. Serta membentuk pedoman berupa strategi dan rencana pengelolaan aset digital yang dimiliki.Keywords: Kampus Digital, Brand Image, Reputasi, Serangan Siber, Manajemen Isu.